Health Care Costs Associated with Hepatitis C: A Longitudinal Cohort Study - Mel Krajden; Margot Kuo; Brandon Zagorski; Maria Alvarez; Amanda Yu; Murray Krahn (Canadian Journal of Gastroenterology)
BACKGROUND: Disease-specific estimates of medical costs are important for health policy decision making.